Natural Convection Mud Type Solar Dryers for Rural Farmers - A. B. Eke; E. A. Arinze (Nigerian Journal of Technological Development, 2011)
A prototype direct mod'e natural convection mud type solar dryer was designed, fabricated and tested. Mud was selected as a major dryer material based on its thermal properties, availability and workability by the rural dwellers who .are the end users. Consequent to the laboratory test which dried maize from initial moisture content of 29 % wet basis to final moisture content of 12 % wet basis, three large scale mud type solar dryers of 400 kg capacity of maize grain, were constructed and each located at Jere, New-Wase and Kwaka, in Kaduna and Niger states of Nigeria respectively.150 kg of maize grain available from the farmers, at 30 % initial moisture content wet basis was dried at a batch in three replicates to 12 % moisture content wet basis, with the dryers. The dried crops were used to evaluate the large .. scale mud solar dryers. The results showed that the dryers achieved SS percent saving in drying time, with high quality dried crops, over the open sun drying. Also, the dryers and oven sun drying methods attained average system drying efficiencies of 45 .6 and 22. 7 percent in the same order. Oral interview conducted to randomized sample of farmers in Jere, New-Wase and Kwaka, showed that the farmers were willing to adopt mud solar dryer for drying their crops, because they normally work with mud, and can afford to own mud type solar dryers.